3,3'-Diindolylmethane and indole-3-carbinol: potential therapeutic molecules for cancer chemoprevention and treatment via regulating cellular signaling pathways - Reyes-Hernandez, Octavio Daniel; Figueroa-Gonzalez, Gabriela; Quintas-Granados, Laura Itzel; Gutierrez-Ruiz, Stephany Celeste; Hernandez-Parra, Hector; Romero-Montero, Alejandra; Sharifi-Rad, Javad (Bmc, 2023)
Dietary compounds in cancer prevention have gained significant consideration as a viable method. Indole-3-carbinol (I3C) and 3,3'-diindolylmethane (DIM) are heterocyclic and bioactive chemicals found in cruciferous vegetables like broccoli, cauliflower, cabbage, and brussels sprouts. They are synthesized after glycolysis from the glucosinolate structure. Clinical and preclinical trials have evaluated the pharmacokinetic/pharmacodynamic, effectiveness, antioxidant, cancer-preventing (cervical dysplasia, prostate cancer, breast cancer), and anti-tumor activities of I3C and DIM involved with polyphenolic derivatives created in the digestion showing promising results. However, the exact mechanism by which they exert anti-cancer and apoptosis-inducing properties has yet to be entirely understood. Via this study, we update the existing knowledge of the state of anti- cancer investigation concerning I3C and DIM chemicals. We have also summarized; (i) the recent advancements in the use of I3C/DIM as therapeutic molecules since they represent potentially appealing anti-cancer agents, (ii) the available literature on the I3C and DIM characterization, and the challenges related to pharmacologic properties such as low solubility, and poor bioavailability, (iii) the synthesis and semi-synthetic derivatives, (iv) the mechanism of anti-tumor action in vitro/in vivo, (v) the action in cellular signaling pathways related to the regulation of apoptosis and anoikis as well as the cell cycle progression and cell proliferation such as peroxisome proliferator-activated receptor and PPAR gamma agonists; SR13668, Akt inhibitor, cyclins regulation, ER-dependent-independent pathways, and their current medical applications, to recognize research opportunities to potentially use these compounds instead chemotherapeutic synthetic drugs.
Keywords: Chemotherapeutic drugs; Indole-3-carbinol (I3C); 3,3'-diindolylmethane (DIM); Cancer; Anti-tumor action